Causal relationships between mitochondrial proteins and different pathological types of lung cancer: a bidirectional mendelian randomization study - Ji, Tanao; Lv, Yue; Liu, Meiqun; Han, Yujie; Yuan, Baochang; Gu, Jun (Frontiers in Genetics, 2024)
An increasing number of studies point to an association between mitochondrial proteins (MPs) and lung cancer (LC). However, the causal relationship between MPs and LC remains unclear. Consequently, our study employed a bidirectional Mendelian randomization (MR) analysis to explore the causal association between MPs and different pathological types of LC. A two-sample MR study was performed using the genome-wide association study (GWAS) data sourced from the IEU Open GWAS project. We applied the primary inverse variance weighted (IVW) method along with additional MR methods to validate the causality between MPs and different pathological types of LC. To ensure the robustness of our findings, sensitivity analyses were employed. Moreover, we performed a bi-directional MR analysis to determine the direction of the causal association. We identified a total of seven MPs had significant causal relationships on overall LC, lung squamous cell carcinoma (LUSC), and small cell lung carcinoma (SCLC). We found two MPs had significant associations with overall LC, four MPs had significant associations with LUSC, and four MPs had significant associations with SCLC. Additionally, an MP was found to have a nominal relationship with LUSC. Moreover, no causality was found between MPs and lung adenocarcinoma (LUAD). Bidirectional MR showed no reverse effect between identified MPs and different pathological types of LC. In general, our findings of this MR study suggest causal associations of specific MPs with overall LC, LUSC, and SCLC. However, no such causality was found in LUAD.